June hayward’s narcissistic personality disorder in r. F. Kuang’s yellowface - Aprilia Larasati; Danu Wahyono (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This research aims to explore June Hayward’s Narcissistic Personality Disorder, including the symptoms, the cause, and the effect. This study uses a psychological approach because the study focuses on the main character’s psychological problem. The symptoms of Narcissistic Personality Disorder are analyzed using DSM-5-TR diagnostic criteria, while the causes and effects are analyzed using Freud’s psychoanalytic theory, supported by psychological journals on NPD. The method used in this study is a qualitative descriptive method to explore the portrayal of Narcissistic Personality Disorder through June Hayward’s character. The findings reveal that June Hayward has eight out of nine symptoms of Narcissistic Personality Disorder. June Hayward’s Narcissistic Personality Disorder symptoms involve envy, lack of empathy, sense of entitlement, exploitative behavior, arrogance, grandiosity, need for admiration, and fantasies of success. The finding also shows that June’s NPD is influenced by June’s unresolved childhood problems, parenting style, and repressed emotions, which cause June Hayward to seek external validation to maintain her self-esteem. Furthermore, the finding also shows how Narcissistic Personality Disorder affects June Hayward’s emotional regulation, interpersonal relationships, and the way June sees the reality of herself. These findings demonstrate how Narcissistic Personality Disorder shapes June's personality and influences the conflicts that develop throughout the novel.